Open Source Software for Data Visualization - Janamanchi, Balaji (Archives of Business Research, 2019)
There is no denying the fact that large amounts of data is generated in almost all our daily activities. With the increased volumes of data there is an acute need for new tools that can help make sense of these large volumes of data and provide useful actionable pointers. As the saying goes, a picture is worth thousand words. So visualizing the data makes it easier to grasp the salient aspects of the data and possibly opens the doors for greater insights. What better way to do it than in the most cost effective way or simply free of cost, at least in terms of purchase or usage costs. Open source software provides such cost free options to process and visualize data. This study analyses the availability and accessibility of Data Visualization software on the Source Forge website, undeniably, a large repository of open source software resources. Limiting the search to Business & Enterprise category, and using “Data Visualization” key word, a total of 42 applications are identified and their data is downloaded and analyzed. It is hoped that the results will help users to be aware of various Data Visualization Open-source software options currently available for use. It is also intended that the results will help users understand the current state of Open Source Data Visualization Software development.